Cyclosporine Lipid Nanocapsules as Thermoresponsive Gel for Dry Eye Management: Promising Corneal Mucoadhesion, Biodistribution and Preclinical Efficacy in Rabbits - Lubna M. Eldesouky; Riham M. El-Moslemany; Alyaa A. Ramadan; Mahmoud H. Morsi; Nawal M. Khalafallah (MDPI AG, 2021)
An ophthalmic cyclosporine (CsA) formulation based on Lipid nanocapsules (LNC) was developed for dry eye management, aiming to provide targeting to ocular tissues with long-term drug levels and maximum tolerability. CsA-LNC were of small particle size (41.9 ± 4.0 nm), narrow size distribution (PdI ≤ 0.1), and high entrapment efficiency (above 98%). Chitosan (C) was added to impart positive charge. CsA-LNC were prepared as in-situ gels using poloxamer 407 (P). Ex vivo mucoadhesive strength was evaluated using bovine cornea, while in vivo corneal biodistribution (using fluorescent DiI), efficacy in dry eye using Schirmer tear test (STT), and ocular irritation using Draize test were studied in rabbits compared to marketed ophthalmic CsA nanoemulsion (CsA-NE) and CsA in castor oil. LNC incorporation in in-situ gels resulted in an increase in mucoadhesion, and stronger fluorescence in corneal layers seen by confocal microscopy, compared to the other tested formulations. Rate of recovery (days required to restore corneal baseline hydration level) assessed over 10 days, showed that CsA-LNC formulations produced complete recovery by day 7 comparable to CsA-NE. No Ocular irritation was observed by visual and histopathological examination. Based on data generated, CsA-LNC-CP in-situ gel proved to be a promising effective nonirritant CsA ophthalmic formulation for dry eye management.